ANALISA PERBAIKAN TANAH DASAR PROYEK PEMBANGUNAN TERMINAL MAINTENANCE FACILITY, TELUK LAMONG, GRESIK - Paksitya Purnama Putra; Indra Nurtjahjaningtyas; Devi Naning (Fakultas Teknik, Universitas Wiraraja, 2023)
Soft soil problems in the Truck Maintenance Facility construction project became a major obstacle in the development process of the project. Soft soil has characteristics with low bearing capacity and compression that lasts a long time and large. One method chosen for the soft soil problem is to combine preloading with Prevebricated Vertical Drain to accelerate the consolidation process to match the age of geotechnical work on the project. Based on the results of soil investigation, improvement of soft soil can be divided into three areas (A, B, C) based on the characteristics and depth of the soft soil. The preloading height varies in each area. Area B requires the highest preloading height of 8.11 meters. The reason is that area B has a large thickness of soft soil. Only preloading in Area B requires special handling in the form of 6 layers of geotextile reinforcement on the embankment. PVD is used in all construction areas. The effective distance for installing the PVD found based on the results of the analysis on the two installation patterns, namely triangles and quadrilaterals, is the same as 2 meters. Therefore, even though the triangular pattern has a faster consolidation time, the rectangular pattern is better to apply because it has effectiveness in field installation.